Analisis Kesalahan Penerapan Qawa'id Pada Buku Ajar Bahasa Arab - Muhammad Afif Amrullah (Universitas Islam Negeri Raden Intan Lampung, 2017)
Still, the presence of errors in the application of qawa''id Arabic Arabic textbook writing in the neighborhood Dikdasmen PWM DIY shows that the preparation of textbooks is not of good quality. This research aims to locate faults textbook writing so that it can immediately be repaired. As of this writing done on the application of qawa'id Arabic in textbook writing. The procedure used:  data collection,  classification or  grouping error,  frequency error  types,  the identification of the scope of the type of error, remedial and identification errors. Artifacts errors found as many as 524 items an error. The error types, divided into two aspects of the  errors,  namely  (1)  Error morphology  (akhta  'al-sarafiyyah)  include isim  gairu munsarif,  jama'  and  fi'il  Muta'adiy,  alif  Layyinah,  and typographical errors.  (2)  a  structural  or syntactic  errors  (akhta  'tarkibiyyah)  include:  na'at  man'ut,  nakirah-ma'rifah,  errors  harokat, miscellaneous  structures,  tarkib  Idafiy  (mudaf-mudaf  ilaih),  tarkib  isnadiy  (mubtada'  khabar), maf'ul  mutlaq,  mabni  fathah,  removal  of  language  elements,  ambiguous, one selected, couples idiom said, adding, writing qat'a glottal stop, and hamzah wasal. Based on the analysis of the textbook errors, some errors are still common, namely the writing section glottal qat'a, isim gairu munsarif, alif Layyinah, writing errors, nakirah-ma'rifah, mabni fathah, and hamzah wasal. Some of the things that cause the occurrence of such errors that is the attitude of carelessness and a disregard for the rules by the author, the inconsistency of the author of  the application  of a  rule,  application of  the rules  are an incomplete  and excessive generalization.